Description and development of the means of a model experiment for load balancing in distributed computing systems; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Nagiyev A. E.; Sherstneva A. I. Anna Igorevna; Botygin I. A. Igor Aleksandrovich; Galanova N. Y. (2016, 2016)
Title screen